Analysis of Circulating Immune Biomarkers by Race in Men With Metastatic Castration-Resistant Prostate Cancer Treated With Sipuleucel-T. (24th July 2021) - Hawley, Jessica E; Pan, Samuel; Kandadi, Harini; Chaimowitz, Matthew G; Sheikh, Nadeem; Drake, Charles G
Abstract: Among racial subgroups, Black men have the highest prostate cancer–specific death rate, yet they also exhibit prolonged overall survival compared with White men when treated with standard therapies, including sipuleucel-T. Differential immune responses may play a role in these observations. We compared circulating immune markers from 54 men (18 Black and 36 White) with metastatic castrate-resistant prostate cancer who received sipuleucel-T and were enrolled on an immune monitoring registry. Markers included longitudinal serum cytokine concentrations, humoral responses, and cellular immunity from baseline until 52 weeks after sipuleucel-T administration. Black men had statistically significantly higher median concentrations of TH 2-type (interleukin [IL]-4, IL-10, and IL-13) and inflammatory cytokines (IL-2, IL-12, and IL-6) compared with prostate-specific antigen-matched White men both at baseline and 52 weeks after sipuleucel-T (2-sided P  <   .05). No differences by race were seen in either the antigen-specific T-cell response or the humoral responses to the immunizing antigen PA2024 and select secondary antigens.